Manifestation of plasmablastic lymphoma in the oral cavity: Report of two cases and literature review - Letícia da Silva Soares Gomes; Caroline Alfaia Silva; André Luiz Carvalho Barreiros; Patrick Rocha Osborne; Jeconias Câmara; Tiago Novaes Pinheiro; Christina Shiang; José Augusto Andrade Godoy Bezerra; Naíza Menezes Medeiros Abrahim; Luciana Botinelly Mendonça Fujimoto (Oral Oncology Reports)
Plasmablastic lymphoma (PBL) is a rare and aggressive non- Hodgkin 's B-cell lymphoma initially reported in patients with the HIV virus with a predilection for the oral cavity. It can affect individuals with other types of immunodeficiency and appear in extra-oral sites, also demonstrating an association with Epstein-Barr Virus (EBV) infection. Histopathological diagnosis is challenging due to overlapping features of other high-grade lymphomas and plasma cell lesions. The objective of the study was to report two cases of oral manifestations of Plasmablastic Lymphoma, in a patient with different HIV serological status and EBV positivity, aiming to present and discuss information regarding the clinical presentation, laboratory and immunohistochemical findings, proposed treatment and a review of updated literature on the topic.